The depiction of the US-China relations and Chinese culture in American cinematography - Novosad, Matěj (2023)
In my thesis, I set out to conduct an Interpretative Discourse Analysis of three selected movies. I focused on the depiction of Chinese and American identities in the movies through the lens of Edward Said´s Orientalism. Through my work I wanted to showcase how China, through its influence on Hollywood, counters Orientalism and to sum degree executes a form of Occidentalism.